If it's not what You are looking for type in the equation solver your own equation and let us solve it.
X/6=9X=
We move all terms to the left:
X/6-(9X)=0
We add all the numbers together, and all the variables
-9X+X/6=0
We multiply all the terms by the denominator
-9X*6+X=0
We add all the numbers together, and all the variables
X-9X*6=0
Wy multiply elements
X-54X=0
We add all the numbers together, and all the variables
-53X=0
X=0/-53
X=0
| n10+7=9 | | 3n+1+31=44 | | 5y-(2(y+1)+2=7y | | 5x-22+3x+42=180 | | 5y+1=37 | | x-(0.5x)=1.5 | | 7=12x-4 | | y=35+125 | | -2+3n=−70 | | -13n-142=-15n | | 2+3n=−70 | | 2+3n=−70n | | 3=18/u | | f =2.5 | | 64/w=4 | | O.12x=1 | | 5y+4=32 | | 1/4(20d+4)=5d+1 | | 3(2a−3)=9 | | 11+4=10+y | | 4.8e−5.76=11.52 | | r(r+4)=780 | | 2x3=-250 | | x*20=120 | | -8j-7=17-14j | | p=2➗2 | | 1/8=5x/22 | | 8j-7=17-14j | | 2b+4=18b= | | 2x2+5x=2 | | 4n-11=24 | | 0.5x+15=2.5x-5 |